2019
DOI: 10.5334/jime.528
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Student Engagement Through Educational Technology: Towards a Conceptual Framework

Abstract: The concept of student engagement has become somewhat of an enigma for educators and researchers, with ongoing discussions about its nature and complexity, and criticism about the depth and breadth of theorising and operationalisation within empirical research. This equally applies to research conducted in the field of educational technology and its application in schools and higher education. Recognising the inherent role that technology now plays in education, and the potential it has to engage students, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(226 citation statements)
references
References 109 publications
7
152
0
2
Order By: Relevance
“…This also includes the careful alignment of theory and methodological design, in order to both adequately analyse the phenomenon under investigation, as well as contributing to the soundly executed body of research within the field of educational technology. Further research is invited in particular into how educational technology affects cognitive and affective engagement, whilst considering how this fits within the broader sociocultural framework of engagement (Bond, 2019a). Further research is also invited into how educational technology affects student engagement within fields of study beyond Arts & Humanities, Education and Natural Sciences, Mathematics & Statistics, as well as within graduate level courses.…”
Section: Recommendations For Future Work and Implications For Practicementioning
confidence: 99%
“…This also includes the careful alignment of theory and methodological design, in order to both adequately analyse the phenomenon under investigation, as well as contributing to the soundly executed body of research within the field of educational technology. Further research is invited in particular into how educational technology affects cognitive and affective engagement, whilst considering how this fits within the broader sociocultural framework of engagement (Bond, 2019a). Further research is also invited into how educational technology affects student engagement within fields of study beyond Arts & Humanities, Education and Natural Sciences, Mathematics & Statistics, as well as within graduate level courses.…”
Section: Recommendations For Future Work and Implications For Practicementioning
confidence: 99%
“…Similarly, a wide range of innovative research methods are demonstrated by doctoral researchers in this field, including analysis of video data (Murphy, Coiro, & Killi, 2019), affective computing approaches (Hillaire, Iniesto, & Rienties, 2019), action research (Boyd, 2019), and mixed methods approaches (Baas, Admiraal, & van den Bert, 2019;Foley & Marr, 2019). We also note the strong conceptual foundation of the works included in this special issue across a wide range of topics, (see Baas, Admiraal, & van den Bert, 2019;Conde Gafaro, 2019;Bond & Bedenlier, 2019).…”
Section: The Special Collectionmentioning
confidence: 89%
“…Altogether, we argue that innovation is present in this research on a number of different levels. The most immediately obvious is the wide range of diverse topics present in this collection, from macro-level focuses on open educational resources (see: Baas, Admiraal, & van den Bert, 2019;Paskevicius & Irvine, 2019), to learning design supports at the institutional level (see: Bond & Bedenlier, 2019;Boyd, 2019;Foley & Marr, 2019;Hillaire, Iniesto, & Rienties, 2019), and students' more micro experiences with various technology-supported curriculum features (see: Conde Gafaro, 2019;Foster, 2019;Murphy, Coiro, & Kiili, 2019), among others. Similarly, a wide range of innovative research methods are demonstrated by doctoral researchers in this field, including analysis of video data (Murphy, Coiro, & Killi, 2019), affective computing approaches (Hillaire, Iniesto, & Rienties, 2019), action research (Boyd, 2019), and mixed methods approaches (Baas, Admiraal, & van den Bert, 2019;Foley & Marr, 2019).…”
Section: The Special Collectionmentioning
confidence: 99%
“…Mode of delivery "distance education" OR "blended learning" OR "virtual universit*" OR "open education" OR "online course*" OR "distance learning" OR "collaborative learning" OR "cooperative learning" OR "game-based learning" that this would seriously limit the ability of the search to return adequate literature, and the decision was made to leave any phrase relating to engagement out of the initial string. Instead, the engagement and disengagement facets that had been uncovered-published elsewhere (Bond and Bedenlier, 2019)-were used to search within the initial corpus of results.…”
Section: Student Engagement: Focus On a Multifaceted Conceptmentioning
confidence: 99%
“…Developing a search string, which is appropriate for the purpose of the review and ensures that relevant research can be identified, is an advanced endeavor in itself, as the detailed account by Campbell et al (2018) shows. Resulting from our initially broad review question, we were subsequently faced with the task to create a search string that would reflect the possible breadth of both student engagement (facets) (see Bond and Bedenlier, 2019) as well as be inclusive of a diverse range of educational technology tools. The educational technology tools were, in the end, identified in a brainstorming session of the three researchers and the guiding professors; trying to be comprehensive whilst simultaneously realizing the limitations of this attempt.…”
Section: Developing the Search String: Iterations And Complexitymentioning
confidence: 99%